Average time taken by a Rheumatology patient to reach a Rheumatologist in Pakistan - Saif, Saba; Rizwana Kithlew (Journal of the Pakistan Medical Association, 2022)
Objective: To study the time taken by individuals from onset of symptoms related to rheumatic diseases to approaching a rheumatologist, and to establish the various delaying factors. Method: The cross-sectional study was conducted at the Department of Medicine, Division of Rheumatology, Combined Military Hospital, Lahore, Pakistan, from August 1 to December 31, 2020, and comprised patients of either gender diagnosed with inflammatory arthritis or other connective tissue diseases. Demographic and clinical data, including antibody status, was recorded. Time lag in visiting a rheumatologist at different levels and factors causing the delay were identified. Data was analysed using SPSS 22. Results: Of the 235 patients, 186(79%) were females and 49(21%) were males. The overall median age was 39 years (interquartile range: 29-50 years.). Of the total, 52(22%) patients presented in <12 weeks of symptom onset to a rheumatologist. Median time for patient-related delay factors was 6 months (interquartile range: 1-12 months), while the median time for physician-related delay was 8 months (interquartile range: 2-42 months). The median time for appointment delay was 1 week (interquartile range: 1-2 weeks). Median duration from the start of symptoms to evaluation by a rheumatologist was 24 months (interquartile range: 6-72 months). The most common delaying factor 131(55.7%) was lack of proper assessment at the primary care level. No association was found between age and time of presentation (p>0.05), but male gender, higher socioeconomic status, education level and rheumatoid factor negativity presented earlier compared to the rest (p<0.05 each). Conclusion: The primary care physician’s delayed ---Continue